A viabilidade das redes de compras para PME'S da contrução civil paranaense - Alves, Joecimara Miquilino (2012)
The cooperation network is defined as a process of abstraction, integration and optimization of energy, resources and skills, capable of generating a relationship system that organizes individuals and businesses equally, around a goal of public character. This network aims at presenting the strategic benefits achieved with the formation of a network of cooperation and understanding of the impacts of their training between small and medium enterprises involved. The objective of this study is to evaluate the evolution of networks in construction procurement Parana. It is characterized by a descriptive exploratory research through case study. We analyzed the network of cooperation "Living Well" located in the western regions, through a sampling of six (06) stores in six (06) cities. The results show that the majority of companies participating in the networks are interested in participating in this partnership, because they can thus have a more comprehensive economic, productive and greater diversity in their products, and lower acquisition cost of their purchases. The main benefits obtained by joining the network were to reduce costs and increase bargaining power with suppliers, as well as, qualification of employees, marketing and financial consulting.